Land Degradation Changes the Role of Above- and Belowground Competition in Regulating Plant Biomass Allocation in an Alpine Meadow - Zhang, Yong; Zheng, Qiuzhu; Gao, Xiaoxia; Ma, Yandan; Liang, Kemin; Yue, Haitao; Huang, Xiaoxia; Wu, Kaiting; Wang, Xiaorong (Frontiers in Plant Science, 2022)
The allocation pattern of plant biomass presents the strategy of the plant community to adopt environmental changes, while the driver of biomass allocation is still unclear in degraded alpine grassland ecosystems. To explore the issue this study investigated the R/S ratio (i.e., shoot to root ratio), plant aboveground traits, and root competition of three functional groups (i.e., grasses, sedges, and forbs) at three degradation levels (i.e., no obvious degradation, ND; moderate degradation, MD; and severe degradation, SD) in an alpine meadow in the Eastern Qinghai-Tibetan Plateau. The relationships among plant aboveground traits, root competition, and R/S ratio were tested by structural equation model (SEM). The results showed that the shoot and root biomass tended to decrease, but the R/S ratio of the plant community did not change along the degradation gradient. Plant height, lateral spread, and leaf length of most plant functional groups reduced, while leaf width and leaf area of most functional groups did not change along the degradation gradients. The root competition ability (presented as the fraction of root biomass in total biomass) of sedges in MD was the lowest, while the grasses was the highest. The effects of aboveground competition on the R/S ratio were non-linear because of the different roles of plant height, lateral spread, and leaf area in regulating the R/S ratio along the degradation gradient. Differently, the effects of belowground competition on the R/S ratio were linear: belowground competition promoted the R/S ratio, and the strength of this effect reduced along the degradation gradient. These results indicate that plant competition might be a critical factor to maintain the high R/S ratio in degraded alpine meadows.